1994
DOI: 10.1002/j.1537-2197.1994.tb15455.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovular development and morphology of the outer integument of Magnolia grandiflora (Magnoliaceae)

Abstract: Ovular development of Magnolia grandiflora was examined to determine the morphology of the outer integument. At the time the ovular primordium begins incurving, the outer integument is initiated subdermally, and later the inner integument arises from the dermal layer. Whereas the inner integument is annular, the outer integument is formed as a semiannular rim interrupted on the concave side of the funiculus. Later the outer integument becomes a hood‐shaped envelope. The obturator is formed as a transversely el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…of Portugal (Friis, Pedersen, and Crane, 1999) have the micropyle-hilum complex, suggesting that ovules with the outer integument hood-shaped already existed in early Cretaceous. Therefore it seems possible that the hood-shaped outer integument is primitive in the Nymphaeales, as has also been argued for other basal angiosperms (Matsui, Imaichi, and Kato, 1993;Umeda, Imaichi, and Kato, 1994;Imaichi, Kato, and Okada, 1995).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…of Portugal (Friis, Pedersen, and Crane, 1999) have the micropyle-hilum complex, suggesting that ovules with the outer integument hood-shaped already existed in early Cretaceous. Therefore it seems possible that the hood-shaped outer integument is primitive in the Nymphaeales, as has also been argued for other basal angiosperms (Matsui, Imaichi, and Kato, 1993;Umeda, Imaichi, and Kato, 1994;Imaichi, Kato, and Okada, 1995).…”
Section: Discussionmentioning
confidence: 71%
“…It has been suggested that the outer integuments are cup shaped and asymmetrical (Bouman, 1984). However, recent developmental and morphological studies have shown that in many basal angiosperms the outer integument is sharply asymmetric and hood shaped, that is, it is lacking on the concave (funicular) side of the ovule (Matsui, Imaichi, and Kato, 1993;Umeda, Imaichi, and Kato, 1994;Imaichi, Kato, and Okada, 1995;Igersheim, 1997, 1999;Endress, 1997, 1998; see also Johri, Ambegaokar, and Srivastava, 1992).The origin of bitegmy has been variously interpreted in contrast to the agreement on the origin of the first (inner) integument by fusion of telomes (Herr, 1995). Crane (1985Crane ( , 1986 and Doyle and Donoghue (1986, 1987) postulated that the outer integument is derived from the leafy lamina of a Caytonialike ancestor, while the carpel enclosing ovules is derived by lateral expansion of its leaf axis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lobed iis have been considered remnants of ancestral integuments or a sign of atavism as paleozoic ovules displayed a lobbed integument [83]. Nevertheless, it has been argued that lobation might have evolved as a way to restrict the circumference of the integument and allow the formation of a micropyle, as an alternative mechanism to distal integument thickening [38].…”
Section: Natural Diversity In Seed Coat Thicknessmentioning
confidence: 99%